Vulnerabilidades, barreiras e cuidados de gestantes usuárias de drogas na cidade de São Paulo - De Souza, Talita [UNIFESP] (2019)
The prevalence of drug use in pregnancy is inaccurate and according to the literature, there are gaps regarding the proposed care and follow-up offered by the care network. In order to support public policies for better care of pregnant women who use drugs, the objective of this study was to describe the vulnerabilities, barriers and ways to care from the perceptions of these women with drug use and in contexts of vulnerabilities and health professionals who works in São Paulo public services. Methods: A qualitative study was conducted using in-depth interviews. Thirteen pregnant women and 12 professionals participated in the study. Data were recorded, transcribed, paired and subjected to Content Analysis and reported based on the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results: The interviewees mentioned numerous vulnerabilities, among them the fragility of family relationships and violence at different social levels. Some of these aspects appear directly related to the identified care barriers, thus showing a dynamic process of vulnerable contexts. The health system and the judiciary represent in the narratives analyzed the main obstacles to comprehensive care, along with the stigma and fear women feel about referring to drug use. The themes identified as possible paths for care are related to the expansion of the provision of care and promotion of possible motherhood, anchored in the assumptions of humanization and integral care. Final considerations: It is important to review models of care, modification and implementation of more adapted services to ensure access, adherence, continuous and comprehensive care of pregnant women who use drugs, as well as policies that ensure human and bioethical right to this population.